Extracorporeal ultrasound exposure by the low-frequency acoustic amplitude-modulated signal on a ureteral stent for preventing its incrustation: experimental determination of optimal application points - A. Yu. Tsukanov; D. S. Akhmetov; A. A. Novikov; N. A. Negrov; A. R. Putintseva; S. P. Semikina (Вестник урологии, 2021)
Introduction. Incrustation and biofilms formation on the surface of ureteral stents are still the most significant complications of internal drainage of the upper urinary tract. There are much researchers conducted to combat these complications. The lack of a solution to this problem affects the ultimate results of treatment and economic losses. The issue of impact by physical methods on the ureteral stent, particularly the use of extracorporeal ultrasound acoustic exposure remains, promising and poorly covered.Purpose of the study. To determine the optimal application points of extracorporeal acoustic exposure by the low-frequency ultrasonic amplitude-modulated signal on a ureteral stent in an experiment.Materials and methods. The original device was designed. The main principle of its operation is the generation of an amplitude-modulated ultrasonic signal in two modes: pulsed and permanent. A sexually mature mongrel dog was an experimental animal. The ureteral stent was placed by laparotomy and cystotomy. Intraoperatively, the emitter of the developed device was applied to the skin of the animal, according to the previously indicated topographic and anatomical landmarks. At the same time, an ultrasonic wave noise analyzer was applied through the laparotomy wound to the appropriate level of the ureter. Measurements of ultrasound intensity indicators were performed three times in two operating modes of the device.Results. Pulsed mode: for the ureteral upper third, the highest ultrasonic intensity (123.67 dB) was achieved along the posterior axillary line. For the ureteral middle third, the best ultrasound intensity (115 dB) was obtained by the posterior axillary line. For the ureteral lower third, the highest ultrasound intensity (113.67 dB) was noted along the middle axillary line.Permanent mode: the best ultrasonic intensity in the projection of the ureteral upper, middle, and lower thirds was achieved along the posterior axillary line and was 118.67 dB, 117 dB and 116.67 dB, accordingly. However, there was an excessive heat effect, manifested by hyperemia and hyperthermia of the animal's skin, fascicular muscle contractions during the instrument functioned in the permanent mode, which can potentially lead to thermal burns and intolerance to the procedure.Conclusion. The pulsed mode of the device function is most safe. The optimal application points of the instrument emitter for the ureteral upper and middle thirds is the posterior axillary line, and for the ureteral lower third is the middle axillary line.